2020
DOI: 10.33411/ijist/2020020102
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Deformation in Lower Jehlum Valley and Eastern Potwar using SRTM DEM

Abstract: This study describes the surface deformation in lower Jehlum and eastern Potwar using remotely sensed Shutter Radar Topographic Mission (SRTM) Digital Elevation Model (DEM) to identify regional uplift rates. Mapping of active surface deformations help to predict seismic hazards. DEMs are the fundamental input factors that identify the surface geometry and its belongings. These belongings include stream offset, elevation, and slope breaks within a contributing area. This study provides an evidence of tectonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…It is a left-lateral strike-slip fault with subordinate reverse motion. The shearing, crushing, fault breccia and gauge are present along the fault zone [38]. Historic data on the occurrence of earthquake events in the region obtained from the USGS showed that the number of earthquakes in the Mirpur and adjacent areas has progressively increased, and a dramatic increase was seen over the last two decades (Figure 3).…”
Section: Geology and Tectonic Settingsmentioning
confidence: 99%
“…It is a left-lateral strike-slip fault with subordinate reverse motion. The shearing, crushing, fault breccia and gauge are present along the fault zone [38]. Historic data on the occurrence of earthquake events in the region obtained from the USGS showed that the number of earthquakes in the Mirpur and adjacent areas has progressively increased, and a dramatic increase was seen over the last two decades (Figure 3).…”
Section: Geology and Tectonic Settingsmentioning
confidence: 99%